Vulnerability and resilience to climate change in fishing communities in Mulegué, México (Revista LIDER, 2020)
This study assesses the capacity and the resilience of the fishing communities in the Mulege Municipality, Northern Pacific, Baja California Sur, Mexico, to adapt to climate change effects, and to resist economic vulnerability through diversification of productive activities. The factors that increase resiliency are consciousness levels regarding the risks that exist in the community, as wekk as high access to the media. The majority of the families own a car and all of them have access to health services. On the negative side count the following factors: lack of shelters in case of extreme events and little leadership by the local government. Almost exclusive dependence on fishing makes economic vulnerability high.